(12+5i)-(9-2i)=0

Simple and best practice solution for (12+5i)-(9-2i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12+5i)-(9-2i)=0 equation:


Simplifying
(12 + 5i) + -1(9 + -2i) = 0

Remove parenthesis around (12 + 5i)
12 + 5i + -1(9 + -2i) = 0
12 + 5i + (9 * -1 + -2i * -1) = 0
12 + 5i + (-9 + 2i) = 0

Reorder the terms:
12 + -9 + 5i + 2i = 0

Combine like terms: 12 + -9 = 3
3 + 5i + 2i = 0

Combine like terms: 5i + 2i = 7i
3 + 7i = 0

Solving
3 + 7i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 7i = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 7i = 0 + -3
7i = 0 + -3

Combine like terms: 0 + -3 = -3
7i = -3

Divide each side by '7'.
i = -0.4285714286

Simplifying
i = -0.4285714286

See similar equations:

| 1.3+5.3=24.2 | | 2(-4y+4)+8y=8 | | 9x^2-30x-525=0 | | 3r-14=-28+r | | -90=9x | | -19+x=-11 | | 5x+25+2x+15=180 | | 68=17n | | -14=n+3 | | (y-6)(9y-7)=0 | | -41-19=15a | | y^3+y^2-5y-x^2=-4 | | x+6+x+9+x+3=x | | 8a-5a-3a+a=20 | | 1=2(5-6x) | | 10v=2(9-2v) | | 11=m+20 | | 3ky-12kz+24kw=0 | | q(q+7)=0 | | 1-4p=-2(5p-1)+5 | | 2x+3y-2=5 | | -15=b-16 | | (2c-9)(c-1)=0 | | 31.25/25= | | 16x^2-36=-72 | | 2(x-7)+5=-9 | | 6s^4t^3-12s^3t^4=0 | | n(n-9)=0 | | 6x+7yx+9y=0 | | y^2+y-112=0 | | j(j-8)=0 | | 25/31.25= |

Equations solver categories